Legal Aspects of Preventing the Circulation of Methamphetamine in Cirebon City - Ghina Nur Afifah; Endang Sutrisno (Syntax Corporation Indonesia, 2026)
The abuse of methamphetamine narcotics in Indonesia, including in Cirebon City, shows a fluctuating trend but tends to be high so that it becomes a serious problem. Indonesia's strategic geographical conditions and the development of technology-based circulation networks have also encouraged the increasing complexity of narcotics crimes. This study aims to analyze legal provisions regarding the prevention of the circulation of methamphetamine narcotics and assess its implementation in practice in Cirebon City. The method used is a normative juridical approach. The results of the study show that Law Number 35 of 2009 has comprehensively regulated prevention efforts through preventive, repressive, and rehabilitative approaches. Implementation by the Cirebon City Police and Cirebon City BNN is carried out through counseling, mapping of vulnerable areas, supervision, enforcement, as well as empowerment and rehabilitation programs. However, its effectiveness is not optimal, characterized by the still high number of cases, the dominance of users, as well as resource constraints and the development of digital-based modus operandi. This condition shows the need to strengthen the implementation of the law that is more adaptive, integrated, and supported by increasing the capacity of the apparatus and active participation of the community to suppress narcotics trafficking in a sustainable manner.